The Responses of Gen Z to the Qur`An-Based Jihad Propagation on the Internet Sites - Wardani, Wardani; Bashori, Bashori; Tasrif, Muh. (Sharia Journal and Education Center Publishing, 2025)
The jihād as a war against non-muslim communities constitutes a global phenomenon. The people of radical thought have used various means to promote their ideas, including the Internet. This article aims to analyze the responses of Gen Z as university students toward interpreting some Qur’anic verses and using images to support the arguments for the necessity of jihād. Employing Wolfgang Iser’s theory of reception and Norman Holland’s theory of psychological reader-response, it concludes first, that although educated in the Quranic interpretation principles, the vast majority of them have accepted those radical interpretations of jihād-verses and have affirmed that war, based on perceived ideological interpretations, is a permanent duty upon Muslim communities; second, that their psychological expression, either happiness, sadness, being shocked, or angry, in various ways of expressed reasons, represent a single goal, e.g., the willingness of performing jihād; third, viewed from their theological motives, that the different faith, in their minds, could be regarded the sufficient reason for war; fourth, that, due to belonging to poor farmer families, one of the possible factors, among others, behind their minds of others as such is an economic factor because it contributes to inadequate education.